Portugal : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper analyzes Portugal's export performance in 2006 and assesses whether it might augur a sustained recovery. The paper examines the factors underlying the recent export rebound, and searches for signs of fundamental changes in structures of the export industries during the last decade. It highlights the importance of labor market flexibility. Using a four-country version of the IMF Global Economic Model, the paper attempts to illustrate the benefits of labor market reform to help close the competitiveness gap.